(untitled) (European Journal of Pure and Applied Mathematics, 2023)
This paper deals with the concept of generalized δ p(Λ,s)-closed sets. Especially, some properties of generalized δ p(Λ,s)-closed sets are discussed. Moreover, we apply the notion of generalized δ p(Λ,s)-closed sets to present and study new classes of spaces called δ p(Λ,s)-T_12-spaces and δ p(Λ,s)-normal spaces. Several properties and characterizations concerning δ p(Λ,s)-T_12-spaces and δ p(Λ,s)-normal spaces are established.